Forgive, not forget: Exploring the influence of perception of dating infidelity to forgiveness behaviour in women - Maharani, Winda; Yundianto, Devie (Jurnal Ilmiah Psikologi Terapan, 2024)
Infidelity in relationships is increasingly common in marriage and dating relationships. Its strong effect on mental health makes this topic worthy of further research, especially in perceptions of dating infidelity relationships. Perceptions of dating infidelity have three dimensions: ambiguous, deceptive, and explicit infidelity. This study uses a quantitative design with a total of 77 women and using convenience sampling. We analyzed using simple regression analysis. Data collection used The Forgiveness Scale and Perception of Dating Infidelity Scale. The results of this study indicate a significant negative effect between the perception of dating infidelity and forgiveness behavior in the women population who are victims of infidelity value F(1,75) = 5,114, p= 0.027, adj. R2= 0.051, and regression coefficient (β=-0,091). Ambiguous behavior F(1,75) = 4,582, p= 0.036, adj. R2= 0.045, and regression coefficient (β=-0,077) and deceptive behavior F(1,75) = 4,035, p= 0.048, adj. R2= 0.038, and regression coefficient (β=-0,054) dimensions have a significant relationship with forgiveness. Whereas explicit behavior is not significant F(1,75) = 1,425, p= 0.236, adj. R2= 0.006, and regression coefficient (β=-0,028). This research is an initial study on the perception of dating infidelity in Indonesia. It can be expected to be helpful as a study material in designing educational activities such as preventing infidelity in marriage preparation.